PENINGKATAN KEMAMPUAN MENERAPKAN NILAI DAN NORMA DALAM PROSES PENGEMBANGAN KEPRIBADIAN MELALUI MODEL PEMBELAJARAN KOOPERATIF SISWA KELAS X.IPS 2 SMA NEGERI 1 PLAOSAN KABUPATEN MAGETAN TAHUN PELAJARAN 2018 / 2019 - Suharti (Pusat Studi Pendidikan dan Kreativitas Guru, 2020)
This study aims to determine the increase in mastery of sociology subject matter in the competency standards of applying values and norms in the personality development process through the cooperative learning model of class X IPS2 students of SMA Negeri 1 Plaosan Magetani Regency in the 2018/2019 academic year. For this reason, the research used is PTK. with three cycles. Each cycle consists of four repeated steps, namely planning, implementing, observing and reflecting. The results of this study are quite good because student learning outcomes have increased from the first cycle to the third cycle. Based on research data, the results of the third cycle can be seen that the average value is 75.74. Students who score> 65 are 32. All students in class X.IPS 2 have increased mastery of sociology subject matter in competency standards applying values and norms in the process of personality development.